Profil Protein Stadium Sporozoit Eimeria tenella Isolat Yogyakarta Melalui Analisis Protein SDS-PAGE (PROTEIN PROFILE OF THE SPOROZOITE OF Eimeria tenella ISOLATES FROM YOGYAKARTA USING SDS-PAGE PROTEIN ANALYSIS) - Tresnani, Galuh; Prastowo, Joko; Nurcahyo, Wisnu; Daryono, Budi Setiadi (Jurnal Veteriner; Vol 13 No 2 (2012), 2013)
Coccidiosis is one of the important diseases in poultry industry. In Indonesia the morbidity of thedisease is between 80 to 90%. A rapid and prompt diagnosis would be one of the essential steps ineradication and control of the disease. The objective of this study is to determine the protein profile ofsporozoite of Eimeria tenella isolated in Yogyakarta using sodium dodecyl sulphate polyacrilamide gelelectrophoresis (SDS-PAGE) protein analysis. Protein analysis was performed in 12% polyacrilamide geland further electrophoresis at 100 volts and over-staining with Coomasie brilliant blue. The resultsshowed that the sporozoite of E. tenella isolated in Yogyakarta contained five proteins with molecularweights of 15, 26, 32, 80, and 91 kDa, respectively.
Keywords: protein profile, SDS-PAGE, Eimeria tenella